Therapeutic significance of hormone receptor positivity in patients with HER-2 positive breast cancer - Kolarova, Iveta; Vanasek, Jaroslav; Odrazka, Karel; Melichar, Bohuslav; Ryska, Ales; Petera, Jiri; Vosmik, Milan; Dolezel, Martin (Biomedical papers, 2019)
Breast cancer with high expression of human epidermal growth factor receptor (HER)-2 represents a biologically and clinically heterogeneous group of neoplastic disorders. Importantly, hormone receptor expression has an effect on biological properties and affects the selection of therapies. On the basis of molecular genetics, four principal subtypes, including luminal A, luminal B, HER2-enriched (HER-2-E), and basal-like can be distinguished. Breast tumors characterized by HER-2 positivity and simultaneous expression of hormone receptors, triple positive breast cancers (TPBC) are of increasing interest owing to the unique biological characteristics associated with complex interactions between HER-2 and hormone receptor signaling pathways. Interactions between hormone receptors and HER-2 explain the decreased efficacy of hormonal therapy in comparison with HER-2-negative patients. The expression of estrogen receptors in HER-2 positive tumors may also be associated with resistance to anti-HER-2 treatment. Multiple available therapeutic options, including hormonal therapy, anti-HER-2 agents and cytotoxic drugs explain favorable prognosis of TPBC. Escalation and de-escalation therapeutic strategies that could result in lower toxicities are being investigated as well as combinations of anti-HER-2 agents with hormonal therapy, immunotherapy, cyclin dependent kinase 4/6 and phosphatidyl inositol-3-kinase inhibitors. Distinction between subtypes of HER-2-positive breast cancer and treatment diversification may result in improved outcomes in TPBC. A response to neoadjuvant therapy may serve in the tailoring of therapy management.
Keywords: breast cancer; estrogen receptor; HER-2